FEATURES OF THE FAMILY MEDIATION IN TERMS OF DIVORCE - Beridze Ketevan; Ketchakmadze Rusudan (Legal Bulletin, 2021)
The article reveals important role of the psychologist as a mediator in family disputes on examples from history and current practice of mediation in Georgia, focusing on activities of the project "Advocacy for the Protection of Children and Youth" implemented on the basis of the psychology clinic at Batumi Shota Rustaveli State University.